From Coordination to Verbal Serialization – the PÓJŚĆ (Serial Verb) Construction in Polish - Andrason, Alexander (Research in Language, 2018)
The present paper studies the PÓJŚĆ gram in Polish – a construction composed of the verb pójść ‘walk’ and another inflected verb. The author demonstrates that the PÓJŚĆ can be represented as a set of stages on the path linking bi-clausality/bi-verbiness and monoclausal/mono-verbiness. Specifically, it spans the section ranging from a non-canonical, less cohesive instantiation of a serial verb construction (SVC) (in which it overlaps with asyndetic coordination) to a canonical instantiation of SVC (in which it complies with the SVC prototype to a large extent). Accordingly, the study corroborates the view that SVCs may derive from asyndetic coordination and, by accumulating properties associated with different parts of the clausality/verbiness continuum, gradually develop towards SVC. This gradualness is not only diachronic, but may also be observed synchronically.